Outcomes of patients treated with durable polymer platinumchromium everolimus-eluting stents: A meta-analysis of randomised trials - Cassese, Salvatore; Ndrepepa, Gjin; Byrne, Robert A.; Kufner, Sebastian; Xhepa, Erion; De Waha, Antoinette; Rheude, Tobias; Colleran, Roisin; Giacoppo, Daniele; Harada, Yukinori; Laugwitz, Karl-Ludwig; Schunkert, Heribert; et al. (EuroIntervention, 2017)
Aims: The durable polymer platinum-chromium everolimus-eluting stent (PtCr-EES) is a new-generation drug-eluting stent (DES) with a platinum-enriched metallic platform developed to improve the percutaneous treatment of patients with coronary artery disease. We sought to investigate the performance of durable polymer PtCr-EES versus other new-generation DES. Methods and results: We undertook a meta-analysis of trials in which patients receiving percutaneous coronary intervention (PCI) were randomly assigned to durable polymer PtCr-EES versus other new-generation DES (other DES). Primary efficacy and safety outcomes were target lesion revascularisation (TLR) and definite/probable stent thrombosis (ST), respectively. Secondary outcomes were myocardial infarction (MI), target vessel revascularisation (TVR), death, cardiac death and longitudinal stent deformation (LSD). A total of 11, 036 patients in seven trials received a PCI with either durable polymer PtCr-EES (n=6, 613) or other DES (n=4, 423). This latter group comprised patients treated with biolimus- (n=325), cobalt-chromium everolimus- (n=1, 940) or zotarolimus-eluting stents (n=2, 158). After a median follow-up of 12 months (interquartile range 12-24), durable polymer PtCr-EES displayed a risk of TLR (odds ratio 0.98, 95% confidence interval [CI]: 0.75-1.29; p=0.90) and definite/probable ST (0.89 [0.55-1.45]; p=0.63) comparable to that of other DES. However, the durable polymer PtCr-EES was associated with a higher risk of LSD (12.05 [1.60-90.71], p=0.02) compared to other DES. There was no significant difference with regard to other secondary outcomes nor was there heterogeneity across trials. Conclusions: At one-year follow-up, the durable polymer PtCr-EES displays a performance comparable to that of other new-generation DES platforms.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Clinical research; Clinical trial; Drug-eluting stent